Revolutionary Mathematics: Transforming Urban Math Classrooms - Lawrence, Milani Efe (My University, 2015)
African American students are deterred from STEM education, especially mathematical education and mathematical careers. The systematic blueprint of the urban education system has resultantly pipelined students into a definitive caste system. Other influences that affect the success of mathematical urban education includes funding and budget disparities, unqualified teachers, lack of racially and ethnically aware pedagogy, psychological factors, such as self-conception and self-efficacy, and the lack of student mentoring and support. This summer, my objectives were to go into an urban community in the Bronx New York and work with the students, their parents and the staff to find solutions for the deficiency of quality urban mathematical education, using the resources the community itself offered. Through weeks of interviews and analysis of math curricula, I was able to get a general idea of how to change urban math classrooms. Most importantly this summer, I found a suppressed passion for teaching, which has completely transformed my plans for the future.
Global Development: Community Based Solutions